Pengetahuan, Sikap, dan Perilaku Terhadap Pengelolaan Limbah Bahan Kimia di Laboratorium Pada Siswa SMK - Desy Sulistiyorini; Eka Rokhmiati Wahyu Purnamasari; Lesnasari Dalimunthe (Poltekkes Kemenkes Padang, 2022)
The existence of activities in the laboratory becomes important for students to conduct experiments or research, and thus, improve their skills and abilities. However, the use of chemical and biological materials in the laboratory will certainly produce chemical and biological waste. The waste generated is potentially hazardous to health and can pollute or damage the environment either directly or indirectly. It is undeniable that laboratory activities can produce various types of waste, such as liquid and solid waste. This study aims to find out what is related to waste management in a private vocational high schools in the city of Bogor. The results showed that there was no relationship between the variables of gender (p value 1.000), training (p value 0.354), knowledge (p value 1.000) and attitudes (p value 0.472) of respondents to the behavior of laboratory waste management. In conclusion, there is no correlation between waste management practices in schools and knowledge, attitudes, student gender, or training experience. To increase student knowledge and awareness about chemical waste laboratories, however, participation in chemical waste laboratory management training is required of students.